2019
DOI: 10.1016/j.jaci.2018.10.066
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid–binding immunoglobulin-like lectin (Siglec) 8 in patients with eosinophilic disorders: Receptor expression and targeting using chimeric antibodies

Abstract: are full-time employees of Allakos, Inc. B. S. Bochner has current consulting and scientific advisory board arrangements with Allakos, Inc, and owns stock in Allakos, Inc; is a coinventor on existing Siglec-8-related patents and thus might be entitled to a share of royalties received by Johns Hopkins University on the potential sales of such products; and is a cofounder of Allakos, Inc, which makes him subject to certain restrictions under university policy (the terms of this arrangement are being managed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…However, the lack of a small molecule binding to Siglec-8 with high affinity and drug-like residence time τ limits therapeutic applications to monoclonal antibodies and polymeric displays of physiological ligands and derivatives thereof. [15,[20][21][22][23][24]34] Here, in an extended study, we identified the pharmacophores of 6'-sulfo-Lewis x (1 a) and successfully developed the high-affinity mimetic 50. Its core is still neuraminic acid, however bearing a carbocyclic mimetic of the Gal moiety in the 2-position and a sulfonamide substituent in the 9-position.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the lack of a small molecule binding to Siglec-8 with high affinity and drug-like residence time τ limits therapeutic applications to monoclonal antibodies and polymeric displays of physiological ligands and derivatives thereof. [15,[20][21][22][23][24]34] Here, in an extended study, we identified the pharmacophores of 6'-sulfo-Lewis x (1 a) and successfully developed the high-affinity mimetic 50. Its core is still neuraminic acid, however bearing a carbocyclic mimetic of the Gal moiety in the 2-position and a sulfonamide substituent in the 9-position.…”
Section: Resultsmentioning
confidence: 99%
“…[19] In summary, Siglec-8 has been identified as a therapeutic target for the treatment of eosinophil and mast cell disorders. [20][21][22][23][24] Natural sialylated glycans generally exhibit only low monovalent affinities (0.5 to 3 mM), which, however, can be substantially improved by a multivalent presentation. [25,26] The development of potent monovalent siglec ligands started from natural glycan ligands and successfully yielded high-affinity ligands for numerous siglecs: thus, high-affinity ligands for Siglec-1, [27] Siglec-2, [8,[28][29][30] Siglec-4, [31,32] Siglec-7 [33] and Siglec-8 [34] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Two different anti-Siglec-8 antibodies were able to induce eosinophil cell death in vitro, particularly in the presence of IL-5 stimulation. 43 In mouse models treatment with anti-Siglec-8 resulted in depletion of IL-5-induced eosinophilia. 43 Moreover, anti-Siglec-8 antibody was shown to reduce both eosinophil and mast cell infiltration in the stomach and small intestine in a mouse model of eosinophilic gastroenteritis.…”
Section: Sialic Acid-binding Immunoglobulin-likementioning
confidence: 99%
“…43 In mouse models treatment with anti-Siglec-8 resulted in depletion of IL-5-induced eosinophilia. 43 Moreover, anti-Siglec-8 antibody was shown to reduce both eosinophil and mast cell infiltration in the stomach and small intestine in a mouse model of eosinophilic gastroenteritis. 44 Very recently, a phase II trial evaluated the potential of anti-Siglec-8 (AK002) in patients with eosinophilic gastritis and enteritis, demonstrating depletion of gastrointestinal tissue eosinophilia and symptom improvement.…”
Section: Sialic Acid-binding Immunoglobulin-likementioning
confidence: 99%
“…For example, the mIgG1 αSiglec‐8 clones 2E2 and 2C4 were successful at ADCC/ADCP in mice, yet mIgG1 is considered functionally similar to hIgG4, which has lower Fc‐mediated killing capacity compared to other isotypes. This is exemplified in a humanized mouse model where human eosinophils are expanded by IL‐5 and treated with hIgG4 αSiglec‐8 (a unique humanized recombinant clone containing the mIgG1 2E2 epitope binding region) that resulted in only intrinsic cell death, yet treatment with hIgG1 was able to induce ADCC 12 . Thus, the roles of species‐specific molecules and IgG/FcγR responses remain to be clarified for both Siglec‐8 and Siglec‐F in mice.…”
Section: Figurementioning
confidence: 99%